Analysis of time consumption of pIane surfaces lapping in assembly operations - Barylski, Adam (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
Analysis ot lapping and microgrinding with carborundum micrograins on single-disc lapping machine are presented in the paper. Machining components are built from steel 100Cr6 and oxide technical ceramics A1203. Machining time and costs operation are subjected to analysis. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)